Female Representation in the Academic Finance Profession - SHERMAN, MILA GETMANSKY; TOOKES, HEATHER E. (Journal of Finance, 2022)
ABSTRACT We present new data on female representation in the academic finance profession. In our sample of finance faculty at top‐100 U.S. business schools during 2009 to 2017, only 16.0% are women. The gender imbalance manifests in several ways. First, after controlling for research productivity, women hold positions at lower ranked institutions and are less likely to be full professors. Results also suggest that they are paid less. Second, women publish fewer papers. This gender gap exists in research quantity, not quality. Third, women have more female coauthors, suggesting smaller publication networks. Time‐series data suggest shrinking gender gaps in recent years.